Circ-0000197 derived from porcine milk small extracellular vesicles promotes intestinal barrier function by sponging miR-429 - Yuxuan Wang; Bilan Chen; Tingzhou Xuan; Kun Ouyang; Jingshen Chen; Hailong Wang; Junyi Luo; Jiajie Sun; Qianyun Xi; Yongliang Zhang; Ting Chen (Journal of Animal Science and Biotechnology, 2025)
Abstract Background As an essential source of nutrients for young mammals, milk possesses a variety of biological functions. Recently identified milk-derived small extracellular vesicles (sEV) have shown potential regulatory effects on intestinal health. Current studies have highlighted the functional roles of milk-derived sEV and their RNA cargo in promoting intestinal health. However, there is a paucity of research demonstrating how milk-derived sEV influence intestinal barrier function through the transport of circRNAs. Results In this study, we aimed to investigate the effects of porcine milk sEV (PM-sEV) circRNA on intestinal barrier function. We systematically identified the circRNAs involved in this process and analyzed the miRNAs through which PM-sEV deliver circRNAs to regulate intestinal barrier function. Our findings revealed that PM-sEV promote the expression of the intestinal tight junction proteins ZO-1 and Occludin, both in vivo (mice) and in vitro (IPEC-J2). When PM-sEV RNA was reduced using ultrasound treatment, their ability to enhance intestinal barrier function was significantly reduced. Bioinformatics analysis showed that circ-0000197, present in PM-sEV, can target miR-429, while miR-429 has the ability to target the 3'-UTR of ZO-1 and Occludin. Furthermore, experiments involving the overexpression or inhibition of the relevant non-coding RNAs (ncRNAs) demonstrated that circ-0000197 significantly enhances intestinal barrier function, whereas miR-429 exerts an inhibitory effect on this function. Overall, our findings identify circ-0000197 in PM-sEV as a crucial circRNA that regulates intestinal barrier function by inhibiting miR-429. Circ-0000197 carried by PM-sEV acts as a competing endogenous RNA (ceRNA) that regulates the expression of ZO-1 and Occludin by sponging miR-429, thereby promoting intestinal barrier function at both the cellular and in vivo levels. Conclusions These findings emphasize the vital role of circRNAs transported through milk-derived sEV in regulating intestinal health, offering new avenues for developing innovative functional milk components. This mechanism also underscores the importance of PM-sEV carrying circ-0000197 in preserving intestinal barrier integrity. Collectively, this study enhances our understanding of the complex regulatory networks involving PM-sEV carrying circRNAs and their impact on intestinal health.